2004
DOI: 10.1172/jci200420483
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation controls diabetes by altering the balance of pathogenic and regulatory T cells

Abstract: The development of autoimmune diabetes in the nonobese diabetic (NOD) mouse results from a breakdown in tolerance to pancreatic islet antigens. CD28-B7 and CD40 ligand-CD40 (CD40L-CD40) costimulatory pathways affect the development of disease and are promising therapeutic targets. Indeed, it was shown previously that diabetes fails to develop in NOD-B7-2 -/-and NOD-CD40L -/-mice. In this study, we examined the relative role of these 2 costimulatory pathways in the balance of autoimmunity versus regulation in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 47 publications
(35 reference statements)
2
56
1
Order By: Relevance
“…Because some of the same costimulatory signals are needed for stimulation of effector T cells and Treg, a small change in level can alter the balance between these two cell types. CD28 and CD40 have disparate effects on inducing these T cell fates in NOD mice, as a loss of CD28 can restore diabetes in CD40L-deficient mice and alters the number of Tregs in those mice (120). …”
Section: Effects Of DC Maturation Thresholds On Development Of Autoimmentioning
confidence: 99%
See 1 more Smart Citation
“…Because some of the same costimulatory signals are needed for stimulation of effector T cells and Treg, a small change in level can alter the balance between these two cell types. CD28 and CD40 have disparate effects on inducing these T cell fates in NOD mice, as a loss of CD28 can restore diabetes in CD40L-deficient mice and alters the number of Tregs in those mice (120). …”
Section: Effects Of DC Maturation Thresholds On Development Of Autoimmentioning
confidence: 99%
“…(134)]. The NOD mouse has been utilized to study several different mechanisms of blocking costimulatory pathways, both genetically and pharmacologically (120, 135, 136). Some of these therapies have been translated for use in type 1 diabetes patients: treatment with CTLA-4-Ig was successful in delaying disease, but was not successful in reversing disease course, with continued loss of C-peptide, a byproduct of insulin processing that is a marker of endogenous insulin production (137, 138).…”
Section: Blocking DC Alterations To Maintain T Cell Tolerancementioning
confidence: 99%
“…T-reg can prevent the proliferation of effector T cells through mechanisms that likely include inhibition of cytokine production and of co-stimulatory pathways [36], as well as induction of tryptophan catabolism [37]. To the extent that replication of HIV virus is accelerated by cell division, it seems reasonable that T-reg might therefore limit virus production.…”
Section: Contribution Of Innate and Adaptive Immune Responses To Elitmentioning
confidence: 99%
“…We previously reported that neuropathy and diabetes occurred with similar kinetics and incidence in NOD-B7-2KO males and females treated with anti-B7-1 mAbs [29,46]. In contrast, we observed a strong gender bias in the development of autoimmunity in NOD-B7-2KO- Idd3 / 5 treated with anti-B7-1 mAbs (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…We previously showed that treatment of NOD-B7-2KO mice with anti-B7-1 mAbs between 2 and 4 wk of age accelerated neuropathy and restored diabetes, reflecting a breakdown in immune regulation likely due to reduced numbers of regulatory T cells (Tregs) [29,46]. Since anti-B7-1-treated NOD-B7-2KO mice develop diabetes and neuropathy with similar incidence and kinetics, we took advantage of this model to compare the influence of Idd3 / 5 and Idd3 / 10 / 18 loci combinations on each disease within the same animal.…”
Section: Resultsmentioning
confidence: 99%